Multifunctional nanoparticles based on a polymeric copper chelator for combination treatment of metastatic breast cancer. (March 2019) - Zhou, Ping; Qin, Jiaqi; Zhou, Ce; Wan, Guoyun; Liu, Yuanyuan; Zhang, Mingming; Yang, Xiaoying; Zhang, Ning; Wang, Yinsong
Abstract: Copper plays an important role in tumor growth and metastasis. Copper chelation has been confirmed to be an effective strategy for breast cancer therapy through antiangiogenesis. In this work, a copper chelating coil-comb block copolymer RGD-PEG- b -PGA- g -(TETA-DTC-PHis) (RPTDH) was synthesized and used to prepare nanoparticles for loading resiquimod (R848), a TLR7 and TLR8 agonist, thus to combine antiangiogenesis and immune activation to treat breast cancer. RPTDH has strong copper-chelating ability and could self-assemble to form spherical nanoparticles with significant pH-sensitivity. R848 was efficiently loaded into RPTDH nanoparticles and exhibited greatly accelerated releases in weakly acid media simulating tumor microenvironment. RPTDH/R848 nanoparticles significantly inhibited the mobility, invasion and vascular tube formation of HUVECs via copper chelation, demonstrating their strong antiangiogenic activity in vitro. Furthermore, RPTDH/R848 nanoparticles remarkably induced the maturation and activation of human plasmacytoid dendritic CAL-1 cells, indicating their immune-activation ability. In breast tumor-bearing mice, RPTDH/R848 nanoparticles displayed excellent targeting ability for both primary breast tumor and lung metastases, and furthermore dramatically suppressed tumor growth and metastasis through copper deficiency-triggered antiangiogenesis and R848-induced immune activation. In summary, RPTDH/R848 nanoparticles can be used as an therapeutic agent against metastatic breast cancer through combining antiangiogenesis and immune activation.